PENINGKATAN HASIL BELAJAR IPAS MATERI SISTEM PENCERNAAN MANUSIA PADA SISWA KELAS V MELALUI PENERAPAN GAME BASED LEARNING - Winda Aulia; Vicky Dwi Wicaksono; Selviari, Selviari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve science and science learning outcomes regarding the human digestive system in class V students through the application of game based learning. The research method used is collaborative Class Action Research with field supervisors and tutors. The subjects of this research were 31 fifth grade students at SDN Dukuh Kupang III/490 Surabaya. Data collection techniques include test instruments and observations. The research consisted of three stages: pre-cycle stage, cycle 1, cycle 2. The percentage of pre-cycle student learning completion was only 19.35% with an average score of 50.48. Student learning outcomes increased in cycle 1 by 64.52% with an average score of 78.39. Cycle 2 learning outcomes increased again to 87.10% with an average score of 89.52. So it can be concluded that the application of game based learning can improve science learning outcomes for class V human digestive system material.